HIV-1 suppression and durable control by combining single broadly neutralizing antibodies and antiretroviral drugs in humanized mice - Horwitz, Joshua A. (National Academy of Sciences, 2013)
Effective control of HIV-1 infection in humans is achieved using combinations of antiretroviral therapy (ART) drugs. In humanized mice (hu-mice), control of viremia can be achieved using either ART or by immunotherapy using combinations of broadly neutralizing antibodies (bNAbs). Here we show that treatment of HIV-1–infected hu-mice with a combination of three highly potent bNAbs not only resulted in complete viremic control but also led to a reduction in cell-associated HIV-1 DNA. Moreover, lowering the initial viral load by coadministration of ART and immunotherapy enabled prolonged viremic control by a single bNAb after ART was withdrawn. Similarly, a single injection of adeno-associated virus directing expression of one bNAb produced durable viremic control after ART was terminated. We conclude that immunotherapy reduces plasma viral load and cell-associated HIV-1 DNA and that decreasing the initial viral load enables single bNAbs to control viremia in hu-mice.